ISLAMIC EDUCATIONAL VALUES IN 29 JUZ HARGA WANITA NOVEL BY MAâMUN AFFANY - Saswita, Yeny (Studia Religia, 2018)
AbstractThis study aims to describe and analyze the existing religious messages in a 29Juz Harga Wanita novel, which is about the value of Islamic Education in Novelby Maâmun Affany. The method used in this study is interpretive research, i.e.research that performs analysis to get the meaning of a phenomenon and aimsto gain a deep understanding, especially the value of Islamic education and itsrelevance in novel 29 Juz Harga Wanita by Maâmun Affany. This study focuseson literature review, which is utilizing the source library to obtain research datawithout doing field research. Make the novel as an educational medium bytaking lessons from the messages contained therein. The data are grouped intothree kinds, namely (1) the data of the faith value in the 29 Juz Harga Wanitanovel which includes (a) faith in God; (b) faith in the books of God; (c) faithin qada and qadar, (2) data of religious devotion values in 29 Juz Harga Wanitanovel that includes (a) Istiqomah (sticking to religion) (b) Ikhtiar (try and pray);(c) obey the prayer; (d) tawaadlu (humble/not arrogant); (e) qonaâah (willingand sufficient for all that is owned); and 3) data of noble values in 29 Juz HargaWanita novel which includes: (a) nobility to Allah, (b) noble character to manthat is to self, family, neighbor, society; and (c) nobility to the environment.As rahmatan lil Alamin, Islam placed women in a glorious place. Islam is areligion that respects and appreciates women and men to God in absoluteterms. There is relevance between the values of Islamic Religious Educationin 29 Juz Harga Wanita novel, with the goal of Islamic religious education thatis to invite humans to do good and avoid bad nature in accordance with thenorms that have been established by Islam. Islam has given a clear conceptabout the procedure or process of a marriage based on the Qurâan and theSunnah as-saheeh.Â Keywords: Value of Islamic Education, 29 Juz Harga Wanita Novel, MaâmunAffany